Peningkatan Keterampilan Anak Asuh Panti Asuhan Melalui Pelatihan Pembuatan Donat Ubi Jalar Ungu - Fitriani Fitriani; Anandita Eka Setiadi (Universitas Muhammadiyah Pontianak, 2018)
One of the programs and activities to equip the teenagers with skills is through the training of making purple sweet potato donuts. The result of these products can be sold to become a source of income. The implementation of training activities for the manufacture of purple sweet potato donuts was conducted in the Orphanage of Tunas Melati Muhammadiyah, Pontianak, which was attended by 35 participants consist of teenagers and orphanages. The atmosphere during the training was quite conducive and interesting. Phase by stage the training was followed by the residents of the orphanage well and they were very enthusiastic about the training. The result of the questionnaire that had been filled by the participants showed that most of them feel happy and enjoy the atmosphere during the training of making purple sweet potato donuts . According to them, the implementation of training activities making purple sweet potato donuts was easy to follow, done and practiced on their own. In addition, the raw materials needed were also easy to obtain and the price was relatively affordable.